2014
DOI: 10.1016/j.mattod.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured and architectured boron nitride from boron, nitrogen and hydrogen-containing molecular and polymeric precursors

Abstract: The controlled synthesis of boron nitride at the nanoscale with predefined and uniform nanostructures and architectures is in general a big challenge, and making full use of these materials in applications still requires great effort. In this article, recent progress on the synthesis of nanostructured and architectured boron nitride involving molecular and polymeric precursors which contain only boron, nitrogen and hydrogen are reviewed. The potential applications of these materials with controlled porosity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 95 publications
1
44
0
1
Order By: Relevance
“…These materials as well as those with a porous structure are not the focus of the present review. They have been reviewed elsewhere [73]. Finally, solid polyborazylenes are probably the most appropriate candidates for shaping processes.…”
Section: Borazine and Polyborazylene-derived Bnmentioning
confidence: 99%
“…These materials as well as those with a porous structure are not the focus of the present review. They have been reviewed elsewhere [73]. Finally, solid polyborazylenes are probably the most appropriate candidates for shaping processes.…”
Section: Borazine and Polyborazylene-derived Bnmentioning
confidence: 99%
“…It can be tailored into 1D nanoribbons, wrapped into nanotubes, stacked into 3D h‐BN crystals and assembled into various 3D structures. The synthesis methods, properties and potential applications of these BN nanostructures have been comprehensively reviewed . It is concluded that the insulating property of h‐BN sheet is robust against the changes in the dimensionality, which severely hinders the applications in functional devices.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] There is also the H-free counterpart, that is, sp 2 boron nitride, BN, which can be found in the amorphous (a-BN), turbostratic (t-BN), rhombohedral (r-BN) and hexagonal (h-BN) phases. [22,23] In the following, we will not distinguish these phases and will use the label BN as representative of the sp 2 hybridization.…”
Section: Introductionmentioning
confidence: 99%